PTU-187 Is Plasma Citrulline Concentration a Reliable Marker for Diagnosis and Clinical Management of Coeliac Disease ?. (4th June 2013) - Papadia, C; Fonaroli, F; Lanzarotto, F; Salemme, M; Sabatino, A Di; Villanacci, V; Corazza, G R; Forbes, A
Abstract : Introduction: In chronic villous atrophy plasma citrulline concentration (PCC) is decreased at the same severity and extent of mucosal lesions of villous architecture. Marsh-Oberhuber classification is conventionally used for grading villous atrophy in coeliac disease and a correlation with plasma citrulline concentrations has been found in pioneering studies. The Corazza-Villanacci classification gives better inter-observer agreement then Marsh-Oberhuber classification. Our primary aim was to correlate PCC to Corazza-Villanacci classification in coeliac disease. We aimed also to yield information in respect of PCC after one year of gluten free diet. Methods: Forty subjects with a diagnosis of acute celiac disease have been studied. Nine out of forty patients were on gluten challenge diet. All patients underwent OGD with multiple biopsies and a blood test for plasma citrulline concentration at baseline and after one year of gluten free diet (GFD). Routine haematological and biochemical investigations were performed including, IgA tTG, IgA EMA and IgA/G antigliadin, ESR, haemoglobin and haematinics, albumin, liver function tests and creatinine. BMI and clinical symptoms were monitored. Histology was interpreted according to Marsh-Oberhuber and Corazza-Villanacci Classification. Plasma citrulline concentration was analysed by High Performance Liquid Chromatography Results: Mean plasma citrulline concentration was lower (15.12 μmol/l) at baseline, in patients with active celiac disease, than in the same group of patients after one year of GFD (16.47 μmol/l) however we did not observe any overall change in citrulline concentration after one year of gluten-free diet. All patients were only partially histopathologically and clinically responsive to one year of GFD. Plasma citrulline concentrations correlated with Villanacci-Corazza classification (P = 0.05) in patients on gluten challenge diet. Patients with a score of 2 had lower citrulline values compared to those with a score of 1, on average 4 units. Correlation was not found between plasma citrulline concentrations and Marsh-Oberhuber classification at baseline and after one year of gluten-free diet. Conclusion: Plasma citrulline concentration may be considered a reliable marker of severity and extent of small bowel villous atrophy in acute coeliac disease, more data are warranted to determine its role in the long-term management. Disclosure of Interest: None Declared.